Insider Trading, Tax Haven Utilisation, Managerial Resource Diversion and the Propensity to Engage in Related Party Transactions: Evidence from Australia - Almutairi, Abdullah Munawir S. (Curtin University, 2023)
The thesis explore the role and influences of RPTs on insider trading, tax havens and managerial resource diversion. Although the FASB states that RPTs may have legitimate commercial purposes, they are most concerned about the nature of non–arm’s length relationships and outcomes. The thesis extend the knowledge of RPTs and their relationship to corporate insiders’ decisions and behaviour in the context of the Australian market.